2022
DOI: 10.1097/rhu.0000000000001837
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefit of Rituximab in Rhupus Patients From a Single-Center

Abstract: Background: Rhupus syndrome is better characterized, but uncertainties remain, and therapeutic management must be defined. The objective was to analyze therapeutic procedures with a focus on biologic disease-modifying antirheumatic drugs (bDMARDs). Methods:This 10-year medical records review was based on diagnosis codes (rheumatoid arthritis [RA] and systemic lupus erythematosus [SLE]) and biological data (anti-CCP testing, anti-dsDNA, and anti-RNP antibodies). Patients fulfilling 2010 ACR/EULAR and 2012 SLICC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Moreover, other studies have shown that, although the presence of ultrasound-detected erosions is not specific to RA, larger erosions in selected joints are highly specific to RA 4 . In our work, we applied the European Alliance of Associations for Rheumatology definition of erosive disease 5 . Furthermore, the application of cluster analysis to better characterize SLE phenotypes revealed that EA was located in a cluster including anticitrullinated protein antibodies (ACPAs) and anticarbamylated protein antibodies 6 .…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, other studies have shown that, although the presence of ultrasound-detected erosions is not specific to RA, larger erosions in selected joints are highly specific to RA 4 . In our work, we applied the European Alliance of Associations for Rheumatology definition of erosive disease 5 . Furthermore, the application of cluster analysis to better characterize SLE phenotypes revealed that EA was located in a cluster including anticitrullinated protein antibodies (ACPAs) and anticarbamylated protein antibodies 6 .…”
mentioning
confidence: 93%
“…In this respect, whereas several preclinical works demonstrated the key role of IL-6 in the pathophysiology of several connective tissue disease, and early studies reported encouraging results with IL-6 inhibitors in these conditions, targeting IL-6–mediated signaling in SLE myositis and primary Sjögren syndrome did not show superiority in clinical responses versus placebo, except for a potentially beneficial effect of tocilizumab on preservation of lung function in systemic sclerosis–associated interstitial lung disease 9 . In the same way, a failure of tocilizumab was also observed in 2 and 8 patients who received this drug in our series of rhupus and RA/systemic sclerosis overlap syndrome, respectively 5,10 . Thus, until sets of biomarkers associated with particular involvement or predictive of treatment response become available, rather than trying to attribute all the manifestations, including EA, to the same disease, it is preferable, in our opinion, to consider overlapping syndromes as real entities for which it is more relevant to propose therapies having shown their effectiveness in both components of the syndrome.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…After reading the article of Rottenberg et al, 1 we found that lupus arthropathy (LA) has been going through a process of conceptual evolution since the first classification criteria for the disease. The misconception that the presence of articular erosion would mark an overlap between systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) still causes many colleagues to attribute severe LA to rhupus 2 .…”
mentioning
confidence: 99%
“…Understanding this evolution (Table) is essential for further research to identify early which SLE patients are at greater risk for the development of Jaccoud-type deformities and those with the worst joint prognosis that should be treated similar to RA patients. Interestingly, we would like to know if Rottenberg et al 1 have tried tocilizumab to manage some of those patients because the identification of interleukin 6 as a possible biomarker for aggressive LA deformities may signify that this drug may be a good choice for arthritis of both diseases 9 . Furthermore, other biomarkers, such as BLyS (B lymphocyte stimulator) and the presence of type I interferon gene signature, 10 may indicate patients with arthritis who, regardless of whether they meet the criteria for RA, SLE, or both, may benefit from new available therapies.…”
mentioning
confidence: 99%